2010
DOI: 10.1097/hjr.0b013e32832d30c4
|View full text |Cite
|
Sign up to set email alerts
|

PTPN1polymorphisms are associated with total and low-density lipoprotein cholesterol

Abstract: Our results suggest that SNPs in the PTPN1 gene are associated with total plasma and LDL cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The two SNPs that were significant only for survival to the age of 95 are locus rs6067484 in the PTPN1 gene, and rs4837525 located in the PAPPA gene. Information on both of these loci is scarce, with only minor A allele of rs6067484 being previously associated with higher levels of total plasma cholesterol and low-density lipoprotein (LDL) cholesterol in men [95].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The two SNPs that were significant only for survival to the age of 95 are locus rs6067484 in the PTPN1 gene, and rs4837525 located in the PAPPA gene. Information on both of these loci is scarce, with only minor A allele of rs6067484 being previously associated with higher levels of total plasma cholesterol and low-density lipoprotein (LDL) cholesterol in men [95].…”
Section: Plos Onementioning
confidence: 99%
“…However, both variants were reported as potential candidates affecting longevity in a paper by Dato et al which examined the association between SNP-SNP interactions and longevity [55]. rs6067484 is an intronic variant of the PTPN1 gene that encodes protein tyrosine phosphatase non-receptor type 1, a suppressor of insulin signalling pathways [95]. The PTPN1 gene is located in the q13.1-q13.2 area of chromosome 20, a region that is gained or amplified in several cancers [96].…”
Section: Plos Onementioning
confidence: 99%
“…To begin with, the minor alleles of three tag SNPs of PTPN1 —rs6067484A/G, rs6020611A/G, and rs1060402A/G—and the major allele at rs3787348G/T have been associated with higher levels of total plasma cholesterol and low-density lipoprotein (LDL) cholesterol in men with a BMI below 26 kg/m 2 [59]. In a previous study, though, the same haplotype showed no effect on different measures of obesity, macronutrient intake, or eating behavior [60].…”
Section: Ptpn1mentioning
confidence: 99%
“…For example, three PTPN1 SNPs have been found to be associated with total cholesterol and LDL in a population of Dutch men [19]. Two PTPN1 SNPs were found to correlate with serum cholesterol and triglyceride levels in a normoglycaemic, nonobese French population [12].…”
Section: Genetics Of Ptpn1 and Human Obesitymentioning
confidence: 99%